Genomic and biosynthetic landscape of high-temperature Daqu microbiome - Mingyue Cheng; Xing Qin; Ying Han; Fanggen Tan; Menglin She; Xue Zhu; Lin Yuan; Mengjing Teng; Xiyang Ou; Sha Luo; Ping Xiang; Liangqiang Chen; et al. (Bioresource Technology, 2026)

Aging and photodegradation of polycyclic aromatic compounds (PACs) emitted from biomass burning under sunlight and ultraviolet radiation - Ya-Jing Li; Zhen-Shan Huang; Yu-Ping Chen; Zhi-Hui Su; Yi-Huan Chen; Yuan Zeng; Yu-Qi Huang; Yu-Feng Guan; She-Jun Chen (Atmospheric Environment, 2026)

Incorporating variable source areas into rainfall-runoff pollutant export modeling for rural residential catchment - Xuan Huang; Xu Yang; Yuhang Zhang; Man Lang; Ping Li; Kebing Chen; Dongli She; Yongqiu Xia (Journal of Hydrology, 2026)

Indoor Thermal Comfort Study of Office Buildings in Cold Regions of China Based on a Database: A Case Study of Beijing, Tianjin, and Dalian - Ping Chen; Xueying Li; Xiaoyi She; Hanyu Zhou; Kai Nan; Ming Zhang (Energy and Buildings, 2026)

Clostridium dalinum: A Novel Lactic Acid Bacterium with Excellent Antioxidant and Anti-inflammatory Functions Through NF-κB, Keap1-Nrf2-ARE Signaling Pathways - Zheng-Qiang Li; Rui Li; Wei Deng; Rui An; Ping Ma; Jun Li; Rong She; Xiao-Yan Yang; Xu Yang; Wen Xiao (Probiotics and Antimicrobial Proteins, 2026)

Amino-functionalized covalent organic framework-carboxylated carbon nanotubes via covalent bonding for sensitive Tau electrochemical immunosensing - Ping He; Wen-Tao Li; A-Min Zhu; Si-Yuan An; Jun-Ping Ma; She-Ying Dong; Yuan-Zhen Zhou; Jun-Jie Zhu (Chemical Engineering Journal, 2026)

Z-scheme heterojunction engineered covalent organic polymer for thermodynamically optimized CO2 photoreduction - Jiaxin Rong; Xuejing Li; Qiang Xu; Jingwei Han; Jing Zhang; Ke Ren; Ping She; Jun-Sheng Qin; Heng Rao (Chemical Engineering Journal, 2025)

Two birds with one stone: S-scheme charge transfer enables simultaneous efficient photocatalytic complete methanation of CO2 and benzimidazole synthesis - Wei Liu; Heng Zhang; Zhe Zhang; Yali Ji; Tiantian Xu; Xusheng Li; Jiao Chen; Mengyao She; Ping Liu; Shengyong Zhang; Jian-Li Li (Chemical Engineering Journal, 2025)

Green synthesis of paulownia flower-derived carbon dots for sensitive fluorescent detection of paclobutrazol - Yi Zhang; Ping Dong; Nina Sun; Xu Wang; Xinshuai She; Yongqian Xu; Qiongzi Wang; Yun Zhang (Food Chemistry, 2025)

Deciphering early molecular responses to benzotriazole ultraviolet stabilizers-induced toxicity using a dose-dependent yeast functional genomics approach - Xinyuan Xu; Linhao Zong; Shasha Zhang; Dake Cao; Ziqi Tang; Dong Chen; Ying Peng; Luhang She; Ping Jin; Xiaowei Zhang; Miao Guan (Environmental Pollution, 2025)

Electrocatalytic upcycling of polylactic acid hydrolysate and simultaneous hydrogen production - Ping He; Jiang-nan Xu; Jia-yang Dou; Bing Xu; She-ying Dong; Ting-lin Huang; Jun-Jie Zhu (Chemical Engineering Journal, 2025)

Facilitated charge transfer of stable multivariate transition Metal-organic frameworks for photocatalytic CO2 reduction - Jiahui Wu; Zhaoguo Xu; Hai Sun; Heng Rao; Ping She; Jun-sheng Qin (Chemical Engineering Journal, 2025)

In situ construction of cobalt phthalocyanine covalent organic polymer on mesoporous graphitic carbon nitride for boosting photocatalytic CO2 reduction - Jiaxin Rong; Qiang Xu; Jingwei Han; Ke Ren; Jing Zhang; Xue Zhao; Ping She; Jun-Sheng Qin; Heng Rao (Chemical Engineering Journal, 2025)

Evaluating the influence of human activities on flood severity and its spatial heterogeneity across the Pearl River Delta - Jing Zhang; Longfei Yu; Jialong Sun; Haibo Liu; Yang Ping; Zhiyong Liu; Yunlong Song; Xiaofeng Hu; Zhenyan She (Science of The Total Environment, 2025)

Nonlinear dynamic response of graphene platelets reinforced cylindrical shells under moving loads considering initial geometric imperfection - Yin-Ping Li; Gui-Lin She (Engineering Structures, 2025)

Confinement of Z-scheme organic-inorganic heterojunction into mesoporous zeolite for efficient photocatalytic solar fuel generation - Mai-Yan Nan; Heng Rao; Ping She; Jun-Sheng Qin (Chemical Engineering Journal, 2024)

Regulated charge transfer by cascade dual Z-scheme heterojunction of HCdS@ZnIn2S4-Cobalt porphyrin for efficient photocatalytic solar fuel production - Tengfei Bao; Chenxi Tang; Shuming Li; Ping She; Heng Rao; Jun-sheng Qin (Chemical Engineering Journal, 2024)

Self-standing Z-scheme structured heterogeneous nanosheet arrays of ZnIn2S4/cobalt porphyrin sulfonate for bifunctional photocatalytic carbon dioxide reduction and antibacterial - Shuming Li; Xuejing Li; Heng Rao; Ping She; Weng-Chon Max Cheong; Jun-Sheng Qin (Chemical Engineering Journal, 2024)

Local microenvironment modulation of zirconium-porphyrinic frameworks for CO2 reduction - Xue Zhao; Chang-Yan Zhu; Heng Rao; Dong-Ying Du; Min Zhang; Ping She; Li Li; Jun-Sheng Qin (Chemical Engineering Journal, 2024)

Effect of using reclaimed water via furrow and subsurface drip systems under alternate partial root-zone irrigation mechanism on crops growth and soil properties - Mahmoud S. Hashem; Wei Guo; Xue-Bin Qi; Ping Li; Ying-jun She; Jiaxin Cui; Tong Li (Irrigation Science, 2024)
The growing population in the face of water scarcity inevitably necessitates the quest for alternative sources of irrigation water, which integrates them with irrigation strategies for improved agricultural productivity to meet the Sustainable Development Goals. A three-year field experiment was conducted in 2017, 2018, and 2019 to investigate the effect of water quality (reclaimed water (RW) and clean water (CW)), irrigation techniques (subsurface drip irrigation (SDI) and furrow irrigation (FUI)), irrigation methods (full irrigation (FI) and alternate partial root-zone irrigation (APRI) (70% ETc)), and their interactions on the fresh fruit yield (FY), irrigation water use efficiency (IWUE), and nitrogen use efficiency (NUE) of tomatoes. Further, electrical conductivity (EC), pH, and organic matter (OM) of soil were evaluated. The experiments were undertaken over three growing spring seasons in a greenhouse at the Chinese Academy of Agricultural Sciences in Henan Province, China. Throughout the three years of this study, the yield, the IWUE, and the NUE values of all treatments under RW were higher than those corresponding values under CW. The trend was the same under SDI as it was under FUI. Statistical analyses revealed that there was no significant effect ( P > 0.05) of water quality, irrigation technique, and irrigation methods on the soil EC, pH, and OM over the three years. In addition, the interaction between the different experimental factors over the three years of the study was not significant. In conclusion, the application of RW under SDI can result in saving CW and increasing productivity without any negative effect on the investigated soil properties. Furthermore, when RW-SDI is used in conjunction with APRI, it can result in increasing IWUE.

High-frequency monitoring during rainstorm events reveals nitrogen sources and transport in a rural catchment - Xuan Huang; Yi Zhu; Han Lin; Dongli She; Ping Li; Man Lang; Yongqiu Xia (Journal of Environmental Management, 2024)

Rapid nanomolar detection of Δ9-tetrahydrocannabinol in biofluids via electrochemical aptamer-based biosensor - Yu Xie; Jin-Ping She; Jia-Xing Zheng; Kalle Salminen; Jian-Jun Sun (Analytica Chimica Acta, 2024)

Forecasting and early warning of bridge monitoring information based on a multivariate time series ARDL model - Bing Qu; Yaolong Huang; Jieqing She; Ping Liao; Xiuying Lai (Physics and Chemistry of the Earth, Parts A/B/C, 2024)

Facet engineering of BiVO4 photocatalyst for the synergetic adsorption and activation of persulfate for organic pollutants degradation - Ling-Ling Zheng; Lei Tian; Dengke Wang; Ying Chen; Qian-Qian Tang; Qiu-Ju Xing; Xiao-Zhen Liu; Dai-She Wu; Jian-Ping Zou (Chemical Engineering Journal, 2023)

Isoptericola croceus sp. nov., a novel actinobacterium isolated from saline–alkali soil - Yu-Ting OuYang; Ai-Ping Lv; Lan Liu; Ting-Ting Li; Yi Zhou; Ting-Ting She; Li-Xiang Cao; Jian-Yu Jiao; Shuang Wang; Wen-Jun Li (Antonie van Leeuwenhoek, 2023)

Source apportionment of heavy metals in soils around a coal gangue heap with the APCS-MLR and PMF receptor models in Chongqing, southwest China - Jie Ma; Zhi-jie Shen; Sheng-lan Wang; Li Deng; Jing Sun; Ping Liu; Ze-lei She (Journal of Mountain Science, 2023)

Calpain-TRPC6 signaling pathway contributes to propofol-induced developmental neurotoxicity in rats - Ying-Jun She; Hai-Ping Xu; Yin Gao; Qiong Wang; Jun Zheng; Xiangcai Ruan (NeuroToxicology, 2023)

Confined Fe single atomic sites on (100) plane of anatase TiO2 nanofibers boost white LED driven Fenton-like norfloxacin degradation - Zhilin Ji; Rongsheng Cai; Wanneng Ye; Ping Lu; Chung-Li Dong; Yu-Cheng Huang; Xilin She; Denys S. Butenko; Yiming Liu; Yukun Zhu; Dongjiang Yang (Journal of Cleaner Production, 2023)

Comparative transcriptome analyses identify genes involved into the biosynthesis of forsythin and forsythoside A in Forsythia suspensa - Wang Jun Yuan; Su Ping Zhang; Zhi Yin He; Yan Xia He; She Qi He; Li Jun Liu; Xin Sun; Qin Li (Functional & Integrative Genomics, 2022)

Correction to: Proteasome-dependent inactivation of Akt is essential for 12-O-tetradecanoylphorbol 13-acetate-induced apoptosis in vascular smooth muscle cells - Yongna Fan; Ping Xie; Hua Zhang; Shubin Guo; Dongfeng Gu; Mingpeng She; HuiHua Li (Apoptosis, 2022)

Characteristics of single atmospheric particles in a heavily polluted urban area of China: size distributions and mixing states - Li Li; Qiyuan Wang; Xu Zhang; Yuanyuan She; Jiamao Zhou; Yang Chen; Ping Wang; Suixin Liu; Ting Zhang; Wenting Dai; Yongming Han; Junji Cao (Environmental Science and Pollution Research, 2019)

New podolactones from the seeds of Podocarpus nagi and their anti-inflammatory effect - Zhe-Ling Feng; Tian Zhang; Jing-Xin Liu; Xiu-Ping Chen; Li-She Gan; Yang Ye; Li-Gen Lin (Journal of Natural Medicines, 2018)

Isolation and characterization of a crude oil degrading bacteria from formation water: comparative genomic analysis of environmental Ochrobactrum intermedium isolate versus clinical strains - Lu-jun Chai; Xia-wei Jiang; Fan Zhang; Bei-wen Zheng; Fu-chang Shu; Zheng-liang Wang; Qing-feng Cui; Han-ping Dong; Zhong-zhi Zhang; Du-jie Hou; Yue-hui She (Journal of Zhejiang University-SCIENCE B, 2015)

Direct cloning, expression of a thermostable xylanase gene from the metagenomic DNA of cow dung compost and enzymatic production of xylooligosaccharides from corncob - Ming-zhe Sun; Hong-chen Zheng; Ling-cai Meng; Jun-she Sun; Hui Song; Yun-juan Bao; Hai-sheng Pei; Zheng Yan; Xiu-qing Zhang; Jing-sheng Zhang; Yi-han Liu; Fu-ping Lu (Biotechnology Letters, 2015)

Risk factors for the Long-Term Efficacy, Recurrence, and Metastasis in Small Hepatocellular Carcinomas - Ye Chen; She-Gan Gao; Jian-Min Chen; Gong-Ping Wang; Zeng-Fang Wang; Bo Zhou; Can-Hui Jin; Yan-Tong Yang; Xiao-Shan Feng (Cell Biochemistry and Biophysics, 2015)

Serum CA242, CA199, CA125, CEA, and TSGF are Biomarkers for the Efficacy and Prognosis of Cryoablation in Pancreatic Cancer Patients - Ye Chen; She-Gan Gao; Jian-Min Chen; Gong-Ping Wang; Zeng-Fang Wang; Bo Zhou; Can-Hui Jin; Yan-Tong Yang; Xiao-Shan Feng (Cell Biochemistry and Biophysics, 2015)

Bernoulli-based random undersampling schemes for 2D seismic data regularization - Rui Cai; Qun Zhao; De-Ping She; Li Yang; Hui Cao; Qin-Yong Yang (Applied Geophysics, 2014)

Separation method for multi-source blended seismic data - Han-Chuang Wang; Sheng-Chang Chen; Bo Zhang; De-Ping She (Applied Geophysics, 2013)

Gas Leakage Prediction Model of Large-Scale Explosions in Hard Rock Based on Quantification Theory - Xin-Zheng Wang; Jian-Jie Chen; Ping Li; Xiao She; Guan-Yi Niu (Transport in Porous Media, 2012)

The influence of water content on soil erosion in the desertification area of Guizhou, China - Jie Zhou; Yi-qun Tang; Xiao-hui Zhang; Tian-yu She; Ping Yang; Jian-xiu Wang (Carbonates and Evaporites, 2012)

Novel Fluorescent Molecular Clips: Selective Recognition Towards Fe3+ in Aqueous Solution - Lin Li; Neng-fang She; Zhuan Fei; Pui-kin So; Yu-zhou Wang; Li-ping Cao; An-xin Wu; Zhong-ping Yao (Journal of Fluorescence, 2011)

Correlation Analysis Between Bone Mineral Density and Serum Element Contents of Postmenopausal Women in Xi’an Urban Area - Shun-Zhi Liu; Hong Yan; Peng Xu; Jian-Ping Li; Gui-Hua Zhuang; Bo-Feng Zhu; She-Min Lu (Biological Trace Element Research, 2009)

Blockade of HERG K+ channel by isoquinoline alkaloid neferine in the stable transfected HEK293 cells - Dong-fang Gu; Xue-lian Li; Zhi-ping Qi; Sha-shan Shi; Mei-qin Hu; Dong-min Liu; Cheng-bai She; Yan-jie Lv; Bao-xin Li; Bao-feng Yang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2009)

Proteasome-dependent inactivation of Akt is essential for 12-O-tetradecanoylphorbol 13-acetate-induced apoptosis in vascular smooth muscle cells - Yongna Fan; Ping Xie; Hua Zhang; Shubin Guo; Dongfeng Gu; Mingpeng She; HuiHua Li (Apoptosis, 2008)

Effect of brassinolide on callus growth and regeneration in Spartina patens (Poaceae) - Zhou Lu; Min Huang; Dong-Ping Ge; Yong-Hua Yang; Xiao-Ning Cai; Pei Qin; Jian-Ming She (Plant Cell, Tissue and Organ Culture (PCTOC), 2003)